What is the Meaning of the Integration of the Cultural Dimension into Schools, According to the Official Discourse of the Province of Quebec? - Côté, Héloïse; Simard, Denis (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2008)
AbstractSince 1992, Quebec’s Ministry of Education1 and Ministry of Culture and Communications have been creating programs designed to integrate a cultural dimension into schools – a process requiring partnerships between teachers and professionals in the cultural domain. This domain comprises the objects and practices pertaining to the realm of arts and aesthetics and the values which are associated with them, namely expressivity, subjectivity, emotions, sensitivity, singularity, imagination, creativity and feelings (Kerlan, 2004). What does this integration mean, according to Quebec’s official discourse? To answer this question, we relied on sociology of justification theory (Boltanski & Thévenot, 1991; Boltanski & Chiapello, 1999, 2002) and used discourse and content analysis to examine Quebec’s official discourse. Our results suggest that this discourse relies on many definitions of culture and justice. This plurality blurs the meaning of the integration of the cultural dimension and requires that teachers delineate it by themselves.